Observation of terahertz-induced dynamical spin canting in orthoferrite magnon by magnetorefractive probing - Takayuki Kurihara; Motoaki Bamba; Hiroshi Watanabe; Makoto Nakajima; Tohru Suemoto (Communications Physics, 2023)
Spin dynamics induced by intense terahertz pulses are commonly observed by magnetooptical effects. Here, we show that magnetorefractive effect provides a second-harmonic magnon signal whose amplitude is comparably strong with the linear component, making it an efficient probe for detecting the inherent nonlinear spin dynamics in orthoferrites.